2005
DOI: 10.1203/01.pdr.0000181376.83137.ed
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nutrient Restriction Reduces Carotid Artery Constriction Without Increasing Nitric Oxide Synthesis in the Late Gestation Rat Fetus

Abstract: Chronic reduction in substrate delivery to the fetus may induce redistribution of fetal cardiac output to maintain nutrient delivery to vital organs, including the brain. Reduced vasoconstriction, in conjunction with increased local synthesis of nitric oxide may contribute to "brain sparing." The authors hypothesized that maternal undernutrition would reduce vasoconstrictor responses in fetal carotid arteries due to increased nitric oxide. Timed pregnant Sprague-Dawley rats were randomized on day 0 of pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
4
2
Order By: Relevance
“…In the present study, birth weight was significantly reduced in both hypoxic and pair-fed offspring in comparison to the control offspring, which supports previous studies in rats (27)(28)(29)(30)(31)(32)(33). Hypoxic and pair-fed offspring were not only of low birth weight but also showed a reduced BMI relative to controls.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, birth weight was significantly reduced in both hypoxic and pair-fed offspring in comparison to the control offspring, which supports previous studies in rats (27)(28)(29)(30)(31)(32)(33). Hypoxic and pair-fed offspring were not only of low birth weight but also showed a reduced BMI relative to controls.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, several studies demonstrated adrenergic-mediated contractions in isolated carotid arteries from fetal and neonatal lambs (26,28) (29). In fetal and neonatal rat carotid arteries, mounted in a pressurized myograph system, adrenergic agonists induced some reduction in lumen diameter (30,31). However our present data indicate that these diameter changes are probably not accompanied by a significant increase in carotid wall tension.…”
Section: Vascular Reactivity Studiescontrasting
confidence: 55%
“…25 For some models of maternal nutrient restriction, impaired contraction to ␣-adrenoceptor stimulation has also been reported in femoral arteries of young male and female offspring 36 and carotid arteries of fetuses. 37 Evidence from growth restriction and maternal undernutrition models indicates that the effect on offspring vascular contraction is variable, region specific, sex dependent, and sometimes agonist specific. 34,[36][37][38] The endothelium plays a central role in the regulation of vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…37 Evidence from growth restriction and maternal undernutrition models indicates that the effect on offspring vascular contraction is variable, region specific, sex dependent, and sometimes agonist specific. 34,[36][37][38] The endothelium plays a central role in the regulation of vascular tone. Endothelial dysfunction is evident in humans born small and in experimental models of growth restriction and maternal undernutrition.…”
Section: Discussionmentioning
confidence: 99%